Corrosion Inhibition of Aluminum Alloy AA6063-T5 by Vanadates: Microstructure Characterization and Corrosion Analysis. Issue 3 (1st January 2018) - Kharitonov, Dmitry S.; Örnek, Cem; Claesson, Per M.; Sommertune, Jens; Zharskii, Ivan M.; Kurilo, Irina I.; Pan, Jinshan
Abstract : Corrosion inhibition of aluminum alloy AA6063-T5 by vanadates (NaVO3 ) in 0.05 M NaCl solution has been investigated by electrochemical and weight loss measurements, and associated with microstructure and Volta potential data. X-ray diffraction, scanning electron microscopy, and energy dispersive spectroscopy analyses confirmed the presence of micrometer-sized Fe-rich Al4.01 MnSi0.74, Al1.69 Mg4 Zn2.31, and FeAl3 intermetallic phases (IMPs) and nanometer-sized CuAl2, ZnAl2, and Mg2 Si precipitates in the microstructure. Scanning Kelvin probe force microscopy measurements showed Volta potential differences of up to 600 mV between the microstructure constituents indicating a high susceptibility to micro-galvanic corrosion, with interphase boundary regions exhibiting the highest propensity to corrosion. Most IMPs had cathodic character whereas some nanometer-sized Mg-rich particles exhibited anodic nature, with large Volta potential gradients within interphase regions of large cathodic particles. Electrochemical potentiodynamic polarization measurements indicated that the vanadates provided mixed corrosion inhibition effects, mitigating both oxygen reduction, occurring on cathodic IMPs, and anodic metal dissolution reaction, occurring on anodic sites, such as Mg2 Si and interphase boundary regions. Electrochemical measurements indicated that the sodium metavanadate inhibitor blocks active metal dissolution, giving high inhibition efficiency (>95%) during the initial exposure, whereas long-term weight loss measurements showed that the efficacy decreases after prolonged exposure.